Bridging the gap between theory and practice in sales education - Mohd, Azielina; K. Devaki, Kanapathi (Faculty of Accountancy, 2025)
Sales and marketing are essential components of any business, directly influencing customer acquisition and retention. However, educational approaches often emphasize theoretical concepts, leaving students with limited practical experience. The SalesPro Racer simulation game was developed to address this gap by providing an innovative, hands-on learning tool for students in the Sales Management course at Polytechnic Port Dickson. This chapter explores the unique features, practicality, and market potential of the SalesPro Racer while emphasizing its environmental and societal impacts.